1991
DOI: 10.1111/j.1365-2826.1991.tb00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin‐lmmunoreactive Neurons in the Rat Medial Preoptic Area are Oestrogen‐Receptive

Abstract: The identity of neurons influenced by oestrogen is critical for the understanding of ovarian steroid actions in the brain. The medial preoptic a r e a (MPOA) contains one of the largest oestrogen-receptive cell populations in the rat brain and participates in several oestrogen-dependent functions, including the regulation of luteinizing hormone (LH) secretion and sexual behaviour. Using double immunostaining procedures with antibodies specific for the oestrogen receptor and neurotensin, a neuropeptide implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…As previously shown by ourselves and others [4,8], a large population of cells in the MPOA have oestrogen re ceptor-1R nuclei. Ihese cells are concentrated rostrally in the AVIA and more caudallv in the region of the periven tricular preoptic nucleus and MPN.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…As previously shown by ourselves and others [4,8], a large population of cells in the MPOA have oestrogen re ceptor-1R nuclei. Ihese cells are concentrated rostrally in the AVIA and more caudallv in the region of the periven tricular preoptic nucleus and MPN.…”
Section: Resultsmentioning
confidence: 58%
“…We do not, at present, know if CGRP is syn thesised by the same preoptic neurones containing GABA or neurotensin. However, unlike neurotensin [8] and GABA [7], the majority of CGRP-IR cells in the fe male MPN are oestrogen-receptive. It is interesting to note that gonadal steroid hormones modulate cells syn thesising CGRP elsewhere in the central nervous system [15] and periphery [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the preoptic area it has been recently demonstrated that 25-50% of the NT-immunoreactive (NT-IR) neurons contain estrogen receptors [19,20]. This coexistence suggests that in the preoptic area NT neurons mediate directly stimulatory effects of ovarian steroids on Gn-RH secretion.…”
mentioning
confidence: 99%
“…In the rat, the preoptic area (POA) contains the largest numbers of ER-IR cells [7] and several studies have been undertaken to establish the neurotransmitters used by estrogen-re ceptive neurons in this area [13][14][15][16] and define their neuroanatomical connections [17][18][19]. Although the LHRH neurons responsible for the LH surge in the rat are known to reside in the POA, they do not possess ERs [15,20] and it is believed that estrogen modulates their activity indirectly.…”
mentioning
confidence: 99%